2010
DOI: 10.1073/pnas.1000066107
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomic β-glucuronidase uncovers a core adaptive function of the human intestinal microbiome

Abstract: In the human gastrointestinal tract, bacterial β-D-glucuronidases (BG; E.C. 3.2.1.31) are involved both in xenobiotic metabolism and in some of the beneficial effects of dietary compounds. Despite their biological significance, investigations are hampered by the fact that only a few BGs have so far been studied. A functional metagenomic approach was therefore performed on intestinal metagenomic libraries using chromogenic glucuronides as probes. Using this strategy, 19 positive metagenomic clones were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
159
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(161 citation statements)
references
References 43 publications
1
159
0
1
Order By: Relevance
“…[14] A novel β-glucuronidase enzymatic activity was also identified in Firmicutes using a functional metagenomic approach. [15] Similarly, xenobiotic-responsive genes involved in pathways related to antibiotic resistance, drug metabolism, and stress response were recently identified. [16] Intestinal microbes can also generate catecholamines that have an effect on gut physiology.…”
Section: Nutrient Metabolism By the Intestinal Microbiotamentioning
confidence: 99%
“…[14] A novel β-glucuronidase enzymatic activity was also identified in Firmicutes using a functional metagenomic approach. [15] Similarly, xenobiotic-responsive genes involved in pathways related to antibiotic resistance, drug metabolism, and stress response were recently identified. [16] Intestinal microbes can also generate catecholamines that have an effect on gut physiology.…”
Section: Nutrient Metabolism By the Intestinal Microbiotamentioning
confidence: 99%
“…Metagenomic studies of fecal microbial communities have indicated that in a healthy adult, this microbiota is composed of several hundred species-level phylogenetic types (phylotypes), although there is considerable interpersonal variation in species composition, even among monozygotic twins (2,3). Nonetheless, shotgun sequencing of fecal community DNA has shown that these different species assemblages contain shared functional features, including the ability to process otherwise indigestible components of our varied diets such as plant polysaccharides (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…Bioanalysis of the sequences allows to identify new enzymes and to model their 3D structures. Once their physiological role determined, these can become a new validated source of druggable targets and will be managed through classical drug discovery processes [91][92][93][94][95].…”
Section: Microbiota As Source Of Novel Drugs Adjuvants and Targetsmentioning
confidence: 99%